Gig Economy and the Future of Work: Opportunities and Challenges in the Modern Economy - Kadua, Nada Cantika Putri (Nomico, 2026)
The rapid expansion of digital platforms has transformed labor market structures and accelerated the rise of the gig economy as a prominent feature of the modern digital economy. Gig work offers flexible, task-based, and platform-mediated employment opportunities that differ substantially from traditional employment arrangements. This study aims to analyze the economic opportunities created by the gig economy, the challenges faced by gig workers, and their implications for the future of work. This study employed a qualitative descriptive method with a descriptive-analytical approach. Data were collected through semi-structured interviews with gig workers, field observations, and documentation of relevant academic and policy sources. The collected data were analyzed using qualitative content analysis, thematic analysis, and comparative interpretation to identify patterns related to flexibility, income opportunity, labor precarity, social protection, and platform governance. The findings show that the gig economy provides major advantages in terms of work flexibility, broader market access, and alternative income generation, making it attractive for youth, women, and workers with limited access to formal employment. However, these opportunities are accompanied by significant challenges, including unstable income, limited social protection, legal ambiguity, algorithmic control, and psychosocial pressure. The discussion indicates that gig work is not merely an innovative labor model but also a site of emerging labor vulnerability in the digital era. In conclusion, the gig economy reshapes the future of work by expanding labor flexibility while simultaneously intensifying the need for adaptive labor regulation and worker protection.